2015
DOI: 10.1097/ta.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of histone deacetylase 6 promotes survival in a rat model of hemorrhagic shock

Abstract: Background Hemorrhage is the leading cause of preventable trauma-related deaths. We have previously shown that treatment with Tubastatin A (Tub A), a histone deacetylase (HDAC) 6 inhibitor, can improve survival in a rodent model of septic shock. The aims of present study were to determine whether selective inhibition of HDAC 6 can promote survival in a model of hemorrhagic shock (HS). Methods Experiment I (survival study): Wistar-Kyoto rats were subjected to hemorrhagic shock (55% volume blood loss), followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 42 publications
(46 reference statements)
1
22
0
Order By: Relevance
“…HDAC6 inhibition resulted in prolonged survival in murine models of hemorrhagic shock and sepsis (8,10,28). However, molecular mechanisms of the protective effects observed by HDAC6 inhibition in those models have yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC6 inhibition resulted in prolonged survival in murine models of hemorrhagic shock and sepsis (8,10,28). However, molecular mechanisms of the protective effects observed by HDAC6 inhibition in those models have yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Tubastatin A is the most effective HDAC6 inhibitor available so far. Tubastatin A has been reported to reduce stress responses and prolong survival in lethal sepsis models (10, 28, 52-54), and tubastatin A also possesses anti-inflammatory, antirheumatic, and neuroprotective effects (8,11,25,45).…”
mentioning
confidence: 99%
“…Tubastatin A has been reported to possess anti-inflammatory effects [2023]. Tubastatin A treatment can prevent stress responses and prolong survival during systemic inflammation [2428].…”
Section: Introductionmentioning
confidence: 99%
“…An acetyl group can be added to a lysine residue by histone acetyl transferases (HATs) and removed by histone deacetylases (HDACs). Based on their structure and homology to yeast histone deacetylases, HDACs are classified into four classes: class I HDACs (HDAC1, 2, 3, and 8); class II HDACs (HDAC4, 5, 6, 7, 9, and 10); class III HDACs (SIRT1-7); and class IV (HDAC11) (8,9). HDACs have been shown to be associated with many cell functions including cell growth, dedifferentiation, and proliferation and apoptosis (24,41) and have become a target for drug development to treat cancer, including acute myeloid leukemia, acute lymphocytic leukemia, multiple myeloma, and breast cancer (43).…”
mentioning
confidence: 99%
“…Increasing evidence has indicated that the function of HDAC6 is not limited to tumorgenesis but also implicated in some chronic diseases such as neurodegenerative diseases, cardiovascular disease, fibrosis, and cystogenesis (3,4,8,11,51). Interestingly, recent studies have shown that HDAC6 activation is also associated with pathogenesis of acute organ/ tissue injury (9,25,38,46). For example, postischemic treat- ment with tubastatin A (TA), a highly selective HDAC6 inhibitor, improved functional recovery, reduced brain infarct volume, and ameliorated neuronal cell death in a rat model of transient middle cerebral artery occlusion (38).…”
mentioning
confidence: 99%